STRATEGI PEMASARAN INOVATIF DALAM PENGELOLAAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KINERJA ORGANISASI DAN PEMASARAN DI ERA DIGITAL - Satriyo, Galih; Khoiruman, Muhamad Alfi (Growth, 2024)
Amid continuing advances in the world of digital marketing, the role of social media as an effective marketing platform is increasingly becoming key, especially for Micro, Small and Medium Enterprises (MSMEs). In facing this challenge, it is important for MSMEs to have human resources (HR) that suit the needs of the digital age. This research examines the urgency of developing human resources in the context of digital marketing, especially to advance the MSME sector in the realm of social media. The focus of this research is to consider the knowledge and skills required by MSME employees in using social media as an effective marketing tool. By implementing appropriate HR development strategies, MSMEs have the opportunity to gain significant benefits, including increased creativity, adaptation to changing trends, and the ability to compete in an increasingly competitive digital marketing era. In the context of human resource development in the digital marketing era to improve the performance of the MSME sector, the importance of special training and access to the latest information and resources are key strategies that must be implemented.